Innate Immune Cells: A Potential and Promising Cell Population for Treating Osteosarcoma - Wang, Zenan; Wang, Zhan; Li, Binghao; Wang, Shengdong; Chen, Tao; Ye, Zhaoming (Frontiers in Immunology, 2019)
Advanced, recurrent or metastasized osteosarcomas remain challenging to cure or even alleviate. Therefore, developing novel therapeutic strategies is urgently needed. Cancer immunotherapy has witnessed great improvement in recent years, including adoptive cellular therapy, vaccination and checkpoint inhibitors, which make it a potential strategy to treat osteosarcoma. The innate immunocyte, as the first line of defense in immune system and the bridge to adaptive immune response, is one of the vital effector cell subpopulations in cancer immunotherapy. Innate immunotherapy has achieved potent antitumor activity in treating hematologic malignancies and some solid tumors including osteosarcoma. Importantly, some immune checkpoints are both expressed on innate and adaptive immune cells, modulating their function in tumor immunity. Therefore, blocking or activating these immune checkpoint-mediated downstream signal paths can effectively improve the therapeutic effect of the innate immune cell-based therapy. In this review, we summarize the current status of the innate immune cell-based therapy for osteosarcoma and the adjuvant strategy to improve their effectiveness.